2016
DOI: 10.7863/ultra.15.08002
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Ultrasound‐Guided Biopsy of Deep Pelvic Masses

Abstract: The purpose of this review is to discuss the rationale and indications for transvaginal ultrasound-guided biopsy. Transvaginal ultrasound-guided biopsy can be a helpful tool for diagnosis and treatment planning in the evaluation of pelvic masses, particularly when the anatomy precludes a transabdominal or posterior transgluteal percutaneous biopsy approach. A step-by-step summary of the technique with preprocedure and postprocedure considerations is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Different approaches (percutaneously, transvaginally, transrectally, and/or transabdominally) can be used for ultrasound-guided biopsy depending on the localization of the lesion. It can be performed in an outpatient setting, after completion of an ultrasound examination, because it does not require any special preparation of the patient, fasting, or anesthesia 3. Although many radiologists are familiar with image-guided percutaneous biopsy techniques, access to lesions located deeply within the female pelvis is often limited by the position of the major vessels, uterus, urinary bladder, ureter, and bowel.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches (percutaneously, transvaginally, transrectally, and/or transabdominally) can be used for ultrasound-guided biopsy depending on the localization of the lesion. It can be performed in an outpatient setting, after completion of an ultrasound examination, because it does not require any special preparation of the patient, fasting, or anesthesia 3. Although many radiologists are familiar with image-guided percutaneous biopsy techniques, access to lesions located deeply within the female pelvis is often limited by the position of the major vessels, uterus, urinary bladder, ureter, and bowel.…”
Section: Introductionmentioning
confidence: 99%
“…For prostate biopsy, antibiotic prophylaxis is well-established when the transrectal approach is used [17]. However, whether antibiotic prophylaxis is necessary for TVUS-guided biopsy remains controversial [4,9]. Nevertheless, previous reports imply that transvaginal procedures may have a risk of infectious complications [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that transrectal ultrasound (TRUS) or transvaginal ultrasound (TVUS)-guided biopsy is useful and safe for sampling intrapelvic lesions [4-9]. According to the literature, the rate of diagnostic biopsies (i.e., those that enable a histologic diagnosis) is roughly 85%-95%.…”
Section: Introductionmentioning
confidence: 99%
“…Every biopsy was performed by one of two experienced physicians (CG, LW) who had worked at least five years at the interventional ultrasound department using US instrument (Logiq E9; GE Healthcare, Chicago, IL, USA). TVUS- and TRUS-guided biopsies were performed in the lithotomy position with empty bladder after sterilization of the vagina and anus (16). The procedure utilized a reusable automatic biopsy gun (Bard Biopsy, Tempe, AZ, USA) compatible with an 18 gauge 15 cm tru-cut needle.…”
Section: Methodsmentioning
confidence: 99%